2007
DOI: 10.1002/jso.20706
|View full text |Cite
|
Sign up to set email alerts
|

Extended Appleby's operation for pancreatic cancer involving celiac axis

Abstract: The extended Appleby's procedure without blood flow of PHA might be feasible and offered a new approach to resection of pancreatic cancer involving CA and/or CHA; the involvement of pancreatic head might not be the contraindication for Appleby's operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…We performed a tangential resection of the portal vein in one of our 5 patients, as in 31/78 patients (39.7%) reported in the literature [7,8,9,10,11,12,13,14,15,16,18,19,20,21,22,24,25,26,28]. The mortality rate after combined CA and portal vein resection was 2/31 patients (6.5%), while it was 0/47 patients after CA resection alone; thus, associating portal vein resection with DP-CAR increases the related mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We performed a tangential resection of the portal vein in one of our 5 patients, as in 31/78 patients (39.7%) reported in the literature [7,8,9,10,11,12,13,14,15,16,18,19,20,21,22,24,25,26,28]. The mortality rate after combined CA and portal vein resection was 2/31 patients (6.5%), while it was 0/47 patients after CA resection alone; thus, associating portal vein resection with DP-CAR increases the related mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Konishi et al [11] reported several complications, such as liver necrosis, liver abscess, gallbladder necrosis and cholecystitis with DP-CAR. Several authors [11,16,18,19,20,24] reported a transient, moderate elevation of hepatic enzymes, with no signs of clinically significant hepatic ischemia. In our experience, as in the more recently published series, carefully evaluating the pulsatility of the proper hepatic artery after occluding the CA and the CHA proximal to the gastroduodenal artery prevented any severe complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations